2017
DOI: 10.1111/joss.12253
|View full text |Cite
|
Sign up to set email alerts
|

Application of the check‐all‐that‐apply method (CATA) to get insights on children's drivers of liking of fiber‐enriched apple purees

Abstract: Developing food products for children requires their involvement since their needs differ from those of adults. Descriptive methods are helpful in defining product's sensory properties that drive consumer's liking but they are not recommended with children. Consequently, finding new approaches to develop food tailored for children is one of the biggest challenges for food companies and sensory and consumer research scientists. This study has a twofold aim: (a) to test the suitability of check-all-that-apply (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 46 publications
(64 reference statements)
6
28
1
1
Order By: Relevance
“…This finding was uncovered even with slight differences in term language presented to both groups. The findings here also suggest that CATA scales may be appropriate for descriptive purposes, a finding that has recently gained merit (Laureati et al, ). Further work with children may be valuable to understand the limits in their CATA abilities.…”
Section: Discussionsupporting
confidence: 64%
“…This finding was uncovered even with slight differences in term language presented to both groups. The findings here also suggest that CATA scales may be appropriate for descriptive purposes, a finding that has recently gained merit (Laureati et al, ). Further work with children may be valuable to understand the limits in their CATA abilities.…”
Section: Discussionsupporting
confidence: 64%
“…Even when samples had a similar overall liking (P2, PL1, and PL3), significant differences were observed in the usage frequency of several sensory terms. This indicates that the CATA method is able to provide more information on which sensory attributes were perceived by a child population to be different from equally‐liked samples, providing more information regarding their drivers of liking (Laureati et al, ). These findings are in line with those reported by Schouteten, De Steur, et al () who examined the possibility of using the CATA response format to obtain discriminatory sensory profiles for speculoos biscuits with a child and teenage population.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with those reported by Schouteten, De Steur, et al () who examined the possibility of using the CATA response format to obtain discriminatory sensory profiles for speculoos biscuits with a child and teenage population. Furthermore, studies working with children and teenagers showed that the CATA response format is able to obtain distinguished sensory profiles for powdered fruit‐flavored juices (Cardinal et al, ), milk desserts (Vidal et al, ), fiber‐enriched apple purees (Laureati et al, ), and grape nectar (Lima, Ares, & Deliza, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations